Genetic variation and outcrossing rate of Dipterocarpus dyeri in the Tan Phu tropical rain forest (Dong Nai), Vietnam - Duc, Nguyen Minh; Duy, Vu Dinh; Hien, Dang Phan; Thanh, Tran Thi Viet; Trang, Nguyen Thi Phuong; Tam, Nguyen Minh (Academia Journal of Biology, 2019)
Dipterocarpus dyeri (Dipterocarpaceae) is widely distributed in lowland rainforests in southeastern Vietnam. Due to over- exploitation and habitat destruction in the 1980s and 1990s, this species is listed as threatened. Understanding the genetic variation and mating rate among D. dyeri population that occurs in forest patches is necessary to establish effectively conservation strategies for this species. To conserve the species in tropical forests, genetic diversity and mating rate were investigated using eight microsatellites (single sequence repeat, SSR) as markers. All of the eight loci were polymorphic. A total of 36 different alleles were observed across the loci screened. The SSR data indicated high genetic diversity (NA = 4.5; HO = 0.542 and HE = 0.667) and high inbreeding value, FIS= 0,182. The mating system parameters were determined using the mixed mating model and the results indicated high outcrossing rate (tm=0.81 and ts=0.675) and lowselfing rate (0.19). Difference of tm-ts value indicated that inbreeding contributed to selfing rate for this species in the Tan Phu tropical rain forest. The results reflected that D. dyeri habitat in this area has been restored and the number of individuals was high, about 500 individuals. However, seedlings were not found so far in this study. These results indicated the importance of conserving of the genetic resources of Dipterocarpus dyeri species in the Tan Phu rain forest. The conservation strategy should include an establishment of an ex-situ conservation site with new big population for this species from all genetic groups, which might improve its fitness under different environmental stresses.